Resilience and academic performance: exploring the link in dental students - Fizzah Ali; Rehan Ahmed Khan; Mahwish Arooj (Journal of the Pakistan Medical Association, 2024)
This study aims to assess the correlation between the resilience level of dental students (preclinical and clinical years) and its effects on their academic performance. It is a correlational research study that was carried out on second, third, and final-year dental students at Lahore Medical & Dental College, Lahore. Academic resilience was judged by using the academic resilience scale (ARS-30). The correlation between resilience and academic performance was established by applying the bivariate Pearson correlation. The mean age of the students was 21.49±1.39 years. Among 196 dental students from different years, 132(67.35%) were females and 64(32.65%) were males. A strong positive correlation was observed between the academic performance and resilience of dental students, i.e. r=0.774. From the results, it can be concluded that there is a positive correlation between academic resilience and academic performance among dental students. Keywords: Resilience, Dental students, Academic performance.